Response of Rock Breaking by High-voltage Electrical Pulse Considering Multi-field Coupling - Pingping RAO; Weikang FENG; Jifei CUI; Peihao OUYANG (工程科学与技术)
This study develops a coupled multi-physics field numerical model of rock breaking under the action of high-voltage electrical pulses based on electrical, thermal, and mechanical theories. Additionally, a coupled electro-thermal-mechanical numerical model that considers electrical breakdown is proposed to describe the fragmentation process of rock under high-voltage electrical pulses. The random distribution model is employed to simulate potential conductive mineral particles in the rock, and the formation of plasma channels during the electrical breakdown process is comprehensively analyzed. The accuracy of the numerical model is verified by comparisons with the experiments. The calculation results indicate that the breakdown field strength is a critical factor in the formation of plasma channels. The rock-breaking process under the influence of high-voltage electrical pulses can be divided into three stages: the initial stage of plasma channel formation, the stage of plasma channel expansion, and the stage of subsequent plasma channel formation. Prior to the formation of the plasma channel, the temperature and stress were approximately 500 K and 10–2 MPa, respectively; when the plasma channel formed, the temperature and stress increased abruptly within a short duration, with the temperature reaching 103 K and the stress reaching 10 MPa. The temperature and stress at the plasma channel continued to rise as the electrical pulse persisted. When the maximum stress exceeded the critical stress strength of the rock, the rock fractured; concurrently, the channel continued to branch and expand, causing extensive damage to the rock. The conductive mineral particles facilitate the formation of plasma channels, and the denser the particle distribution, the more favorable the channel formation. The longer the duration for the pulse voltage to reach its peak, the relatively faster the rate of damage in the rock-breaking process. The calculation results of the numerical model improve the understanding of the rock-breaking process during the high-voltage electrical pulse.